Pengembangan Bahan Ajar Berbasis QR Code untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran PAI di SMAN 15 Surabaya - Nurrahma, Faizah; Fuad, Ah. Zakki; Sutikno, Sutikno (Jurnal Keislaman, 2025)
This research is a type of development research or Research and Development (R&D) with the ADDIE development model. Data collection techniques in this study were through questionnaires, interviews, and documentation. Data obtained from the questionnaire were analyzed descriptively qualitatively and quantitatively. The results of the study showed that the development of QR Code-based teaching materials was carried out through five stages, namely analysis, design, development, implementation, and evaluation. The results of the development of these teaching materials are suitable for use as teaching materials in class X in the PAI subject at SMAN 15 Surabaya. Student learning interest in the experimental class reached 87.26% with a very good category while the control class reached 81% with a very good category. So, the percentage of learning interest in the experimental class is greater than the control class. The development of QR Code-based teaching materials to increase student learning interest in the PAI subject at SMAN 15 Surabaya can be seen from the results of the unpaired sample t-test analysis through the SPSS version 26 application with a significance level of 0.05 obtained Sig. (2-tailed) of 0.000 (0.000 <0.05). So Ha is accepted and H0 is rejected, meaning that the development of QR Code-based teaching materials can increase students' interest in learning Islamic Religious Education subjects in class X at SMAN 15 Surabaya.